Layered nanofiller-reinforced polyketone composites - Lee, Juchul; Lee, Kwang Hoon; Kim, Daehum; Lim, Soonho; Lee, Sang-Soo (POLYMER SOC KOREA, 2013)
For the polyketone-based composite employing layered nanofillers such as organoclay prepared by melt processing, the effects of layered nanofillers on morphology, structural and mechanical properties of the composites were examined in terms of nanofiller concentration and processing condition. Polyketone clearly exhibited certain degree of intercalation, although highly suppressed in certain cases, and organoclay modified with hydrophilic intercalant molecules showed a much higher interaction with polyketone, resulting in more uniform dispersion of organoclay within polyketone matrix, and correspondingly notable improvement of mechanical properties.
Keywords: CATALYZED ALTERNATING COPOLYMERIZATION; CLAY NANOCOMPOSITES; MELT-INTERCALATION; BEHAVIOR; SURFACES